Study Of The Legal Responsibility Of Developers For The Provision Of Public Facilities And Social Facilities - M.Ali Iskandar; Rafli Wahyu Indrianto; Moh Abyan Nurfikri; Agus Dimyati; Anom Sutrisno (PT Publikasiku Academic Solution, 2024)
The enforcement of law is an integral aspect of the legal system's functioning, and it is often criticized with phrases like